2008
DOI: 10.1177/1059840508326747
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Number of Hours of Sleep in High School Students Who Took Advanced Placement and/or College Courses and Those Who Did Not

Abstract: This study investigated the association between sleep deprivation and enrollment in Advanced Placement (AP) and/or college courses among high school students. Approximately 4,000 surveys were distributed, and 2,197 completed surveys were returned from students in Grades 9 to 12 at 15 high schools in Iowa. Findings indicated the majority of high school students were sleep deprived. Sleep deprivation was significantly associated with enrollment in AP/college courses. Results indicated that enrollment in AP/colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Changing academic demands during the high school years increase the vulnerability for insufficient sleep for many students. Jin and Shi (2008) compared sleep duration between students enrolled in advanced placement (AP)/college courses ( N = 352) and students not enrolled in AP/college courses ( N = 1,708). Their results revealed that students enrolled in AP/college courses slept 40 min to 1 hr less than students not enrolled in AP/college courses.…”
Section: Resultsmentioning
confidence: 99%
“…Changing academic demands during the high school years increase the vulnerability for insufficient sleep for many students. Jin and Shi (2008) compared sleep duration between students enrolled in advanced placement (AP)/college courses ( N = 352) and students not enrolled in AP/college courses ( N = 1,708). Their results revealed that students enrolled in AP/college courses slept 40 min to 1 hr less than students not enrolled in AP/college courses.…”
Section: Resultsmentioning
confidence: 99%
“…Participants in the current study indicated that they commonly responded to academic stress through sleeping for different purposes (i.e., to recharge, to escape). Coping by seeking sleep may be a unique strategy among this population given the risk for sleep deprivation among AP and IB students, as Jin and Shi (2008) demonstrated based on results from a statewide survey of high school students in college-level classes (including AP) who reported sleeping significantly less than their peers in general or honors-level courses. Furthermore, Jin and Shi also found that students with multiple college-level courses got less sleep than peers with fewer college-level classes.…”
Section: Discussionmentioning
confidence: 99%
“…Ferrara and De Gennaro 50 define optimal sleep as "the daily amount of sleep that allows a subject to be fully awake (i.e., not sleepy) and able to sustain normal levels of performance during the daytime" whereas Engle-Friedman et al 51 define optimal sleep as "the amount of sleep required to feel refreshed in the morning." Other studies 52,53 with impressive circularity define optimal sleep as the amount recommended by authorizing bodies. These definitions, however, may be considered inadequate.…”
Section: Can We Define Optimal Sleep?mentioning
confidence: 99%